2011
DOI: 10.1111/j.1440-1797.2010.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

High incidence and recurrence of transitional cell carcinoma in Taiwanese patients with end‐stage renal disease

Abstract: The data shows that Taiwanese patients with ESRD had high incidence (0.9%) and recurrence (35.7%) of TCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…It has been shown that patients who underwent renal transplant in Taiwan had a high cumulative incidence of TCC [33], accounting for 50% of all malignancies occurring after transplantation. In the present study, the cumulative rate of TCC in all ESRD patients was compatible with that of patients with previous reports [34,35]. Because of the late onset of TCC in these patients, long-term follow-up is highly suggested, especially for patients with a previous history of upper urinary tract urothelial carcinoma [36].…”
Section: Discussionsupporting
confidence: 78%
“…It has been shown that patients who underwent renal transplant in Taiwan had a high cumulative incidence of TCC [33], accounting for 50% of all malignancies occurring after transplantation. In the present study, the cumulative rate of TCC in all ESRD patients was compatible with that of patients with previous reports [34,35]. Because of the late onset of TCC in these patients, long-term follow-up is highly suggested, especially for patients with a previous history of upper urinary tract urothelial carcinoma [36].…”
Section: Discussionsupporting
confidence: 78%
“…In Asia, UC of the bladder (UCB) is the major cancer affecting MHD patients [8,16]. In the present study, for the first time, we showed that shorter HDD is an independent risk factor for the occurrence and recurrence of UCB, although the SIR of bladder cancer in maintenance hemodialysis patients has been reported to be higher than that of their healthy counterparts [7].…”
Section: Discussionmentioning
confidence: 67%
“…In particular, Chen et al reported a high frequency of UC in uremic patients [17]. Several hypotheses are proposed to explain this finding, including impaired DNA repair ability, immune defects, nutritional deficiencies, and chronic urinary tract infection [2,8,16]. Wu et al evaluated 73 patients with upper urinary tract urothelial carcinoma (UUT-UC) on dialysis therapy and identified a high recurrence rate in these patients [12].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Physicians who are taking care of hemodialysis patients and renal transplant recipients should be highly alert with presence of hematuria which warrants detailed study of the entire urinary system and image study of the native and transplanted kidneys Tai et al, 2009;Liao et al, 2004). Only 19.4% of patients had history of long-term consumption of Chinese herbs and 3.1% had history of using analgesic compounds (Wang et al, 2011). Contamination of drinking water is considered to be another carcinogenic factor.…”
Section: Urothelial Carcinoma In Hemodialysis Patients and Renal Tranmentioning
confidence: 99%